Sum up to 16 terms of the series $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots $ is
\[\begin{align}
& A.450 \\
& B.456 \\
& C.446 \\
& \text{D}.\text{None of these} \\
\end{align}\]
Answer
Verified
463.2k+ views
Hint: For solving the sum of 16 term series $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots $ we will first find ${{n}^{th}}$ term of the series denoted by ${{T}_{n}}$. Then we will find a sum of n terms of series denoted by ${{S}_{n}}$ using $\sum{{{T}_{n}}}$. We will use following formula for solving this sum,
(1) ${{1}^{3}}+{{2}^{3}}+{{3}^{3}}+\cdots \cdots +{{n}^{3}}=\sum{{{n}^{3}}}\text{ and }\sum{{{n}^{3}}}$ is equal to ${{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}$.
(2) For an AP, $a,a+d,a+2d,\ldots \ldots a+\left( n-1 \right)d$ sum of n terms is given by $\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right)$.
(3) $\sum \left( {{a}_{n}}+{{b}_{n}} \right)=\sum {{a}_{n}}+\sum {{b}_{n}}$.
(4) Sum ${{1}^{2}}+{{2}^{2}}+{{3}^{2}}+\cdots \cdots +{{n}^{2}}=\sum{{{n}^{2}}}$ is equal to $\dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{6}$.
(5) Sum $1+2+3+\ldots \ldots n=\sum n$ is equal to $\dfrac{n\left( n+1 \right)}{2}$.
(6) Sum $1+1+1+\ldots \ldots n=\sum 1$ is equal to n.
Then we will put the value of n as 16 to get our final answer.
Complete step-by-step solution
Here, we are given the series as $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots $.
Let us first find the ${{n}^{th}}$ term of the series, for this, we will find ${{n}^{th}}$ term of numerator and denominator separately.
For numerator, ${{n}^{th}}$ term will be ${{1}^{3}}+{{2}^{3}}+{{3}^{3}}+\cdots \cdots +{{n}^{3}}=\sum{{{n}^{3}}}$ which is equal to $\sum{{{n}^{3}}}$.
As we know $\sum{{{n}^{3}}}={{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}$.
So, number of ${{n}^{th}}$ term is ${{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}$.
For denominators, since all odd terms are adding, so ${{n}^{th}}$ term will be $1+3+5+\ldots \ldots +\left( 2n-1 \right)$.
As we can see, this is an AP with the first term (a) as 1 and a common difference d(3-1=5-3=2) as 2. So let us find the sum of n terms of this AP. Since the sum of n terms of an AP is given by ${{S}_{n}}=\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right)$.
So, we get,
${{S}_{n}}=\dfrac{n}{2}\left( 2+\left( n-1 \right)2 \right)\Rightarrow \dfrac{n}{2}\left( 2n \right)={{n}^{2}}$.
Hence the denominator of ${{n}^{th}}$ term is ${{n}^{2}}$.
So our ${{n}^{th}}$ term of series denoted by ${{T}_{n}}$ is $\dfrac{{{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}}{{{n}^{2}}}\Rightarrow {{T}_{n}}=\dfrac{{{n}^{2}}{{\left( n+1 \right)}^{2}}}{4{{n}^{2}}}=\dfrac{{{\left( n+1 \right)}^{2}}}{4}$.
Since ${{\left( a+b \right)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab$ so,
\[\begin{align}
& {{T}_{n}}=\dfrac{{{n}^{2}}+1+2n}{4}=\dfrac{{{n}^{2}}}{4}+\dfrac{1}{4}+\dfrac{2n}{4} \\
& \Rightarrow {{T}_{n}}=\dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4} \\
\end{align}\]
Now we need to find sum of n terms of a series where ${{n}^{th}}$ term is ${{T}_{n}}=\dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4}$.
So we just need to find $\sum{{{T}_{n}}}$.
Let us denote the sum of n terms by ${{S}_{n}}$. Hence,
${{S}_{n}}=\sum{{{T}_{n}}}\Rightarrow {{S}_{n}}=\sum{\left( \dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4} \right)}$.
As we know, $\sum \left( {{a}_{n}}+{{b}_{n}} \right)=\sum {{a}_{n}}+\sum {{b}_{n}}$ so we get:
\[\begin{align}
& {{S}_{n}}=\sum{\dfrac{{{n}^{2}}}{4}}+\sum{\dfrac{n}{2}}+\sum{\dfrac{1}{4}} \\
& \Rightarrow {{S}_{n}}=\dfrac{1}{4}\sum{{{n}^{2}}}+\dfrac{1}{2}\sum{n}+\dfrac{1}{4}\sum{1} \\
\end{align}\]
Now we know that, sum of squares of n terms is given by $\sum{{{n}^{2}}}=\dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{6}$.
Also, the sum of n terms is given by \[\sum{n}=\dfrac{n\left( n+1 \right)}{2}\].
And the sum of $1+1+1+\ldots \ldots n$ is given by $\sum 1=n$.
So putting all these values we get:
\[\begin{align}
& \Rightarrow {{S}_{n}}=\dfrac{1}{4}\left( \dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{6} \right)+\dfrac{1}{2}\left( \dfrac{n\left( n+1 \right)}{2} \right)+\dfrac{1}{4}\left( n \right) \\
& \Rightarrow {{S}_{n}}=\dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{24}+\dfrac{n\left( n+1 \right)}{4}+\dfrac{n}{4} \\
\end{align}\]
Now, we need to find sum of first 16 terms, so putting n = 16, we get:
\[\begin{align}
& \Rightarrow {{S}_{16}}=\dfrac{16\left( 16+1 \right)\left( 2\left( 16 \right)+1 \right)}{24}+\dfrac{16\left( 16+1 \right)}{4}+\dfrac{16}{4} \\
& \Rightarrow {{S}_{16}}=\dfrac{16\times 17\times 33}{24}+\dfrac{16\times 17}{4}+4 \\
\end{align}\]
Simplifying we get:
\[\begin{align}
& \Rightarrow {{S}_{16}}=374+68+4 \\
& \Rightarrow {{S}_{16}}=446 \\
\end{align}\]
Hence sum of 16 terms of $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots $ is 446.
Hence option C is the correct answer.
Note: Students should know formulas of summation of some of the series such as $\sum n,\sum {{n}^{2}},\sum {{n}^{3}}$. Here we have not taken a sum of 16 sums directly as it would cause high calculations. Always try to make a general solution for the sum of a series and then put the value as 16. Here we have taken ${{S}_{n}}=\sum {{T}_{n}}$ which means we will take sum of all ${{T}_{n}}$ starting from 1 to n. Since ${{T}_{n}}=\dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4}$ which is equivalent to $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots \dfrac{{{n}^{3}}}{\left( 2n-1 \right)}$.
(1) ${{1}^{3}}+{{2}^{3}}+{{3}^{3}}+\cdots \cdots +{{n}^{3}}=\sum{{{n}^{3}}}\text{ and }\sum{{{n}^{3}}}$ is equal to ${{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}$.
(2) For an AP, $a,a+d,a+2d,\ldots \ldots a+\left( n-1 \right)d$ sum of n terms is given by $\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right)$.
(3) $\sum \left( {{a}_{n}}+{{b}_{n}} \right)=\sum {{a}_{n}}+\sum {{b}_{n}}$.
(4) Sum ${{1}^{2}}+{{2}^{2}}+{{3}^{2}}+\cdots \cdots +{{n}^{2}}=\sum{{{n}^{2}}}$ is equal to $\dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{6}$.
(5) Sum $1+2+3+\ldots \ldots n=\sum n$ is equal to $\dfrac{n\left( n+1 \right)}{2}$.
(6) Sum $1+1+1+\ldots \ldots n=\sum 1$ is equal to n.
Then we will put the value of n as 16 to get our final answer.
Complete step-by-step solution
Here, we are given the series as $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots $.
Let us first find the ${{n}^{th}}$ term of the series, for this, we will find ${{n}^{th}}$ term of numerator and denominator separately.
For numerator, ${{n}^{th}}$ term will be ${{1}^{3}}+{{2}^{3}}+{{3}^{3}}+\cdots \cdots +{{n}^{3}}=\sum{{{n}^{3}}}$ which is equal to $\sum{{{n}^{3}}}$.
As we know $\sum{{{n}^{3}}}={{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}$.
So, number of ${{n}^{th}}$ term is ${{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}$.
For denominators, since all odd terms are adding, so ${{n}^{th}}$ term will be $1+3+5+\ldots \ldots +\left( 2n-1 \right)$.
As we can see, this is an AP with the first term (a) as 1 and a common difference d(3-1=5-3=2) as 2. So let us find the sum of n terms of this AP. Since the sum of n terms of an AP is given by ${{S}_{n}}=\dfrac{n}{2}\left( 2a+\left( n-1 \right)d \right)$.
So, we get,
${{S}_{n}}=\dfrac{n}{2}\left( 2+\left( n-1 \right)2 \right)\Rightarrow \dfrac{n}{2}\left( 2n \right)={{n}^{2}}$.
Hence the denominator of ${{n}^{th}}$ term is ${{n}^{2}}$.
So our ${{n}^{th}}$ term of series denoted by ${{T}_{n}}$ is $\dfrac{{{\left( \dfrac{n\left( n+1 \right)}{2} \right)}^{2}}}{{{n}^{2}}}\Rightarrow {{T}_{n}}=\dfrac{{{n}^{2}}{{\left( n+1 \right)}^{2}}}{4{{n}^{2}}}=\dfrac{{{\left( n+1 \right)}^{2}}}{4}$.
Since ${{\left( a+b \right)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab$ so,
\[\begin{align}
& {{T}_{n}}=\dfrac{{{n}^{2}}+1+2n}{4}=\dfrac{{{n}^{2}}}{4}+\dfrac{1}{4}+\dfrac{2n}{4} \\
& \Rightarrow {{T}_{n}}=\dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4} \\
\end{align}\]
Now we need to find sum of n terms of a series where ${{n}^{th}}$ term is ${{T}_{n}}=\dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4}$.
So we just need to find $\sum{{{T}_{n}}}$.
Let us denote the sum of n terms by ${{S}_{n}}$. Hence,
${{S}_{n}}=\sum{{{T}_{n}}}\Rightarrow {{S}_{n}}=\sum{\left( \dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4} \right)}$.
As we know, $\sum \left( {{a}_{n}}+{{b}_{n}} \right)=\sum {{a}_{n}}+\sum {{b}_{n}}$ so we get:
\[\begin{align}
& {{S}_{n}}=\sum{\dfrac{{{n}^{2}}}{4}}+\sum{\dfrac{n}{2}}+\sum{\dfrac{1}{4}} \\
& \Rightarrow {{S}_{n}}=\dfrac{1}{4}\sum{{{n}^{2}}}+\dfrac{1}{2}\sum{n}+\dfrac{1}{4}\sum{1} \\
\end{align}\]
Now we know that, sum of squares of n terms is given by $\sum{{{n}^{2}}}=\dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{6}$.
Also, the sum of n terms is given by \[\sum{n}=\dfrac{n\left( n+1 \right)}{2}\].
And the sum of $1+1+1+\ldots \ldots n$ is given by $\sum 1=n$.
So putting all these values we get:
\[\begin{align}
& \Rightarrow {{S}_{n}}=\dfrac{1}{4}\left( \dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{6} \right)+\dfrac{1}{2}\left( \dfrac{n\left( n+1 \right)}{2} \right)+\dfrac{1}{4}\left( n \right) \\
& \Rightarrow {{S}_{n}}=\dfrac{n\left( n+1 \right)\left( 2n+1 \right)}{24}+\dfrac{n\left( n+1 \right)}{4}+\dfrac{n}{4} \\
\end{align}\]
Now, we need to find sum of first 16 terms, so putting n = 16, we get:
\[\begin{align}
& \Rightarrow {{S}_{16}}=\dfrac{16\left( 16+1 \right)\left( 2\left( 16 \right)+1 \right)}{24}+\dfrac{16\left( 16+1 \right)}{4}+\dfrac{16}{4} \\
& \Rightarrow {{S}_{16}}=\dfrac{16\times 17\times 33}{24}+\dfrac{16\times 17}{4}+4 \\
\end{align}\]
Simplifying we get:
\[\begin{align}
& \Rightarrow {{S}_{16}}=374+68+4 \\
& \Rightarrow {{S}_{16}}=446 \\
\end{align}\]
Hence sum of 16 terms of $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots $ is 446.
Hence option C is the correct answer.
Note: Students should know formulas of summation of some of the series such as $\sum n,\sum {{n}^{2}},\sum {{n}^{3}}$. Here we have not taken a sum of 16 sums directly as it would cause high calculations. Always try to make a general solution for the sum of a series and then put the value as 16. Here we have taken ${{S}_{n}}=\sum {{T}_{n}}$ which means we will take sum of all ${{T}_{n}}$ starting from 1 to n. Since ${{T}_{n}}=\dfrac{{{n}^{2}}}{4}+\dfrac{n}{2}+\dfrac{1}{4}$ which is equivalent to $\dfrac{{{1}^{3}}}{1}+\dfrac{{{1}^{3}}+{{2}^{3}}}{1+3}+\dfrac{{{1}^{3}}+{{2}^{3}}+{{3}^{3}}}{1+3+5}+\cdots \cdots \dfrac{{{n}^{3}}}{\left( 2n-1 \right)}$.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE